Smoking cessation strategies: An in-depth analysis of nicotine replacement therapy and alternatives - Mrozek, Łukasz; Hajduk, Aleksandra; Puchalski, Krzysztof; Zwolski, Maciej; Szumlas, Zuzanna; Klocek, Konrad; Kostecki, Bartosz; Jurek, Aleksander; Nowak, Artur (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The primary objective of this literature review is to thoroughly investigate the topic of nicotine replacement therapy, considering the latest discoveries and detailing various forms of available nicotine substitution. Materials and methods: Literature review of PubMed and Google Scholar databases. State of Knowledge: Tobacco smoking remains one of the leading causes of premature death worldwide, accounting for millions of deaths each year. Nicotine, the addictive component of tobacco, is responsible for sustaining cigarette smoking patterns and making smoking cessation particularly challenging. Nicotine replacement therapy (NRT) is now considered one of the primary methods to help individuals quit smoking by reducing withdrawal symptoms and cravings associated with cessation. Conclusions: Over the years, extensive research has confirmed the effectiveness and safety of NRT, resulting in the development of different forms of nicotine substitution. The outcomes of using these various forms are similar and premature discontinuation by patients remains a primary reason for NRT failure. Therefore, it is crucial for each patient to select the form of NRT that meets their individual preferences. The best results are obtained by combining multiple forms of substitution simultaneously, as well as integrating them with other therapeutic methods.